Pengaruh Word Of Mouth, Brand Image, dan Country Of Origin Terhadap Keputusan Pembelian Smartphone Android Merek Samsung: Studi Kasus Pada Sekolah Tinggi Ilmu Ekonomi Widya Gama Lumajang - Maulidiyah, Siti Naifatul; Lukiana, Ninik (Jurnal Ilmu Manajemen Advantage, 2017)
The purposive of this study is to determine the influence of word of mouth, brand image, and country of origin purchase decision Samsung smartphone android brand in partial and simultaneous. Respondents are 48, analysis of data using multiple linear regression analysis, tested the basic assumptions and hypothesis testing. Result of this research showed that in partially word of mouth and brand image has positive significant effect on purchasing decision, brand image has positive and significant effect on purchasing decision, and country of origin has negative and significant effect on purchasing decision, and simultaneously showed that word of mouth, brand image, and country of origin of effect on purchasing decisions android smartphone brand Samsung. The purchase decision of Samsung smartphone android can be explane by word of the mouth, brand image and country of origin by 27% (coefession determinant). The remaining 73% can be explained by another variable can’t be examined on this research, example is product quality dan price.